2022
DOI: 10.1073/pnas.2203057119
|View full text |Cite
|
Sign up to set email alerts
|

Trade-offs of lipid remodeling in a marine predator–prey interaction in response to phosphorus limitation

Abstract: Phosphorus (P) is a key nutrient limiting bacterial growth and primary production in the oceans. Unsurprisingly, marine microbes have evolved sophisticated strategies to adapt to P limitation, one of which involves the remodeling of membrane lipids by replacing phospholipids with non-P-containing surrogate lipids. This strategy is adopted by both cosmopolitan marine phytoplankton and heterotrophic bacteria and serves to reduce the cellular P quota. However, little, if anything, is known of the biological conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…A similar phenomenon was shown previously in a bacteria-protist grazer scenario. Bacteria which undergo PlcP-mediated lipid remodelling in response to low phosphorus were less likely to be captured by grazers but became more susceptible to digestion once captured [ 29 ]. Similarly, it appears aminolipid formation, which is independent of the PlcP-mediated lipid remodelling pathway, confers a competitive advantage in the form of nutrient uptake, but exerts trade-offs by rendering the cell more prone to bacteriophage infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar phenomenon was shown previously in a bacteria-protist grazer scenario. Bacteria which undergo PlcP-mediated lipid remodelling in response to low phosphorus were less likely to be captured by grazers but became more susceptible to digestion once captured [ 29 ]. Similarly, it appears aminolipid formation, which is independent of the PlcP-mediated lipid remodelling pathway, confers a competitive advantage in the form of nutrient uptake, but exerts trade-offs by rendering the cell more prone to bacteriophage infection.…”
Section: Discussionmentioning
confidence: 99%
“…The aminolipid-deficient mutant is less susceptible to phage attachment We have previously shown that PlcP-mediated membrane lipid remodelling imposes trade-offs for the survival of Phaeobacter sp. MED193 [29]. To further understand the ecological importance of these aminolipids, we compared the ability of phage DSS3-Phi2, the first known bacteriophage to infect Ruegeria pomeroyi DSS-3 [26], to bind to the WT and the olsA mutant.…”
Section: Replacement Of Aminolipids By Pg Affects the Abundance Of Me...mentioning
confidence: 99%
“…In PNAS, Guillonneau et al. ( 1 ) report experiments that demonstrate a rather intricate trade-off in the predator–prey relationship between a bacterium and its protozoan predator. Trade-offs link positive to negative changes in fitness and therefore constrain the paths of evolution as well as the biodiversity, structure, and function of existing food webs.…”
mentioning
confidence: 99%
“…Guillonneau et al.’s ( 1 ) study addresses a response strategy to phosphorus (P) limitation found in many prokaryotes: the substitution of phospholipids with sulfolipids ( 9 ), reducing their requirement for P. Since this only occurs under P limitation, the substitution seems to have a fitness cost, only worth paying when P is a scarce commodity. Both lipid groups are surface-active compounds, and the reduction in P requirement likely comes with the side effect of a change in cell surface properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation